The Analysis of Recount Text Written by Expert and Students - Siti Maryam; Neng Mustika; Rasi Yugafiati (PROJECT (Professional Journal of English Education), 2020)
Retelling the past experiences in the form of recount text is one of the competencies that should be mastered by the students in verbal or written form. Based on the preliminary observation  in SMAN 4 Cimahi, the 10th grade students have no difficulties  in retelling their past experiences orally. To overcome that problem, this research aims to investigate some pedagogical implication needed  in enhancing students’ writing ability in retelling past experiences in form of recount text. This research belongs to qualitative descriptive using the document analysis as a technique to collect the data. The expert document of personal recount text was taken from the electronic book of English for 10th grade of senior high school published by the Ministry of Education and Culture. The finding showed that the expert’s text had genre, register, generic structure, and language features that were in line with the general characteristics of recount text. However, the analysis of student’s text showed that the students found difficulties in delivering and organizing ideas in every stage of Recount text, the content of writing was not totally fulfiiled the linguistic features required. Moreover vocabularies were still great boundaries in the writing. The pedagogical implication proposed is that using concept map. Keywords:  Expert Text, Genre Analysis, Recount Text